Coleridge, Language and the Sublime - Stokes, C. author. aut Link
VII, 211 p.
Keywords: Traversing the themes of language, terror and representation, this is the first study to engage Coleridge through the sublime, showing him to have a compelling position in an ongoing conversation about finitude. Drawing on close readings of both his poetry and prose, it depicts Coleridge as a thinker of 'the limit' with contemporary force.